Polycystic Ovary Syndrome Markers and Mechanism - Kurniawati, Erna Yovi; Pramono, Noor; Hidayat, Syarief Thaufik; Mahati, Endang (Faculty of Medicine, 2024)
Polycystic ovary syndrome (PCOS) is a complex endocrine disorder characterized by hormonal imbalances, metabolic dysregulation, and reproductive abnormalities. This study aims to elucidate the significance of PCOS markers and their mechanisms while outlining the methodology employed. A comprehensive literature review was conducted from 2020 to 2023 using databases like PubMed, ScienceDirect, EMBASE, and Google Scholar. Key search terms included